Analisis Pelaksanaan Konseling oleh Apoteker di Apotek Komunitas - Khandy, Evanda Ratna Thalia; Utami, Wahyu; Rahem, Abdul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze factors that influence the implementation of counseling by pharmacists in community pharmacies in the Malang Regency area. The method used was observational research carried out cross-sectionally using a questionnaire instrument. The research results show a significant relationship (p<0.05) for each independent variable with the implementation of counseling. In conclusion, the availability of infrastructure is the variable that has the most decisive influence on the performance of counseling by pharmacists, followed by the variables of attitude, knowledge, and policy. Keywords: Pharmacist, Pharmacy, Counseling, Pharmaceutical Services